Social Engagement Care for Frail Older Persons: Desire for It and Provision by Live-In Migrant Caregivers. (5th May 2017) - Cohen-Mansfield, Jiska; Golander, Hava; Iecovich, Esther; Jensen, Barbara
Abstract: Objectives: To describe social engagement care (SEC) provided by live-in migrant caregivers for frail older adults compared with care recipients' and families' wishes for such care. Method: Interviews with care recipients, family members, and migrant caregivers assessed preferences for and provision of five types of SEC activities: knowing the older person as a person, knowing their main concerns, having personal conversations, going for walks, and sharing social or leisure activities. Results: Care recipients and family proxies reported a moderate desire for SEC from migrant caregivers, except for sharing leisure activities, for which there was only a slight preference. Migrant caregivers reported these practices at somewhat higher levels compared with the other respondents. Migrant caregivers' reports of practice show little relationship with care-recipients' preferences, but care recipients tended to perceive practice as agreeing with their own wishes. Discussion: It is important to include SEC as part of the role of live-in migrant caregivers of older persons. However, there is a need to differentiate among types of SEC and subsequently optimize the match between the care-recipient's wishes and needs and the actual care provided.